2017
DOI: 10.3390/s17122717
|View full text |Cite|
|
Sign up to set email alerts
|

A Functionalized Tetrakis(4-Nitrophenyl)Porphyrin Film Optical Waveguide Sensor for Detection of H2S and Ethanediamine Gases

Abstract: The detection of hydrogen sulfide (H2S) and ethanediamine, toxic gases that are emitted from industrial processes, is important for health and safety. An optical sensor, based on the absorption spectrum of tetrakis(4-nitrophenyl)porphyrin (TNPP) immobilized in a Nafion membrane (Nf) and deposited onto an optical waveguide glass slide, has been developed for the detection of these gases. Responses to analytes were compared for sensors modified with TNPP and Nf-TNPP composites. Among them, Nf-TNPP exhibited sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 57 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…Our understanding at that time was to determine the total number of hydrogen atoms of the compound according to the ratio of the number of spectral areas. Consequently, the authors wish to at this time make the following corrections to the paper: 1 Figure S1); this result is in good agreement with previous reports [42,43]. In order to further characterize the purity of the material, we carried out an elemental analysis measurement.…”
supporting
confidence: 81%
See 4 more Smart Citations
“…Our understanding at that time was to determine the total number of hydrogen atoms of the compound according to the ratio of the number of spectral areas. Consequently, the authors wish to at this time make the following corrections to the paper: 1 Figure S1); this result is in good agreement with previous reports [42,43]. In order to further characterize the purity of the material, we carried out an elemental analysis measurement.…”
supporting
confidence: 81%
“…The obtained responses showed that the reversibility of the sensing film was affected by interfered gases (Supplementary Materials Figure S7). The complete recovery of the sensing film could not be achieved and the baseline also varied" (page 11, lines 5-14 in our paper published in Sensors [1]).…”
mentioning
confidence: 98%
See 3 more Smart Citations